Jack Wade Creek: An in situ Alaskan Late Pleistocene Vertebrate Assemblage - Porter, Lee (ARCTIC, 1986)
Sixty Late Pleistocene vertebrate fossils have been recovered from an inferred in situ sedimentary section of a placer mine near Jack Wade, east-central Alaska. The fossil assemblage, called the Jack Wade fauna, is composed of the partial remains of 18 animals, of which 11 are Ovis sp. cf. O. dalli Nelson (Dall sheep). 3 Bison priscus (Bojanus) (Steppe Bison), 2 Rangifer tarandus (Linnaeus) (Caribou), 1 Equus (Asinus) lambei Hay (Yukon Wild Ass) and 1 Alces alces (Linnaeus) (Moose). The assemblage is noteworthy in two respects: it is one of few Late Pleistocene in situ assemblages known from Eastern Beringia and it is composed of large ungulates exclusively. Of these, a uniquely large proportion are mountain sheep.Key words: Beringia, Pleistocene, fauna Mots clés: Béringie, pléistocène, faune